Obligate symbiont involved in pest status of host insect - Hosokawa, Takahiro (The Royal Society, 2007)
The origin of specific insect genotypes that enable efficient use of agricultural plants is an important subject not only in applied fields like pest control and management but also in basic disciplines like evolutionary biology. Conventionally, it has been presupposed that such pest-related ecological traits are attributed to genes encoded in the insect genomes. Here, however, we report that pest status of an insect is principally determined by symbiont genotype rather than by insect genotype. A pest stinkbug species, Megacopta punctatissima, performed well on crop legumes, while a closely related non-pest species, Megacopta cribraria, suffered low egg hatch rate on the plants. When their obligate gut symbiotic bacteria were experimentally exchanged between the species, their performance on the crop legumes was, strikingly, completely reversed: the pest species suffered low egg hatch rate, whereas the non-pest species restored normal egg hatch rate and showed good performance. The low egg hatch rates were attributed to nymphal mortality before or upon hatching, which were associated with the symbiont from the non-pest stinkbug irrespective of the host insect species. Our finding sheds new light on the evolutionary origin of insect pests, potentially leading to novel approaches to pest control and management.